2009
DOI: 10.1002/marc.200900316
|View full text |Cite
|
Sign up to set email alerts
|

On the Quantitative Click Conjugation of Molecular Weight Distributions: What Can Theoretically Be Expected?

Abstract: The assessment of the success of a click conjugation for block copolymer formation often occurs via ill-defined criteria based on the qualitative shape of the size exclusion chromatography (SEC) distribution as well as unsuitable characteristics of these molecular weight distribution such as the peak molecular weight, M(p) . The data presented herein illustrate that from the shape of the SEC distribution, w(log M) versus log M, of the click product-under the assumption of a 100% efficient conjugation reaction-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 32 publications
(19 reference statements)
1
46
0
1
Order By: Relevance
“…As proposed by Barner-Kowollik, the number average molecular weight (M n ) serves as sensitive indicator of the success of the conjugation reaction. [30] As expected, the molecular weight of the block-copolymer (3-b-6) (PMMA-equivalent: M n ¼ 11 400 g Á mol À1 ) effectively is the sum of the molecular weights of the individual building blocks (3) (M n ¼ 3 800 g Á mol…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…As proposed by Barner-Kowollik, the number average molecular weight (M n ) serves as sensitive indicator of the success of the conjugation reaction. [30] As expected, the molecular weight of the block-copolymer (3-b-6) (PMMA-equivalent: M n ¼ 11 400 g Á mol À1 ) effectively is the sum of the molecular weights of the individual building blocks (3) (M n ¼ 3 800 g Á mol…”
mentioning
confidence: 89%
“…It is known however, that SEC results need to be judged with some care when accessing the efficiency of polymer-polymer conjugations. [30] Especially in the current case where two polymers of differing polydispersity and molecular weight are reacted, SEC may draw a skewed picture. As proposed by Barner-Kowollik, the number average molecular weight (M n ) serves as sensitive indicator of the success of the conjugation reaction.…”
mentioning
confidence: 98%
“…46 For observation of changes in polymer endgroups and conjugation points, no better analytical method exists to this date. This characterization approach is also especially useful for the present study where the macromonomers are conjugated via multi-thiol core molecules (see Scheme 2), thus leading to the formation of homopolymers with distinct topology.…”
Section: Synthesis Of Butyl Acrylate Macromonomermentioning
confidence: 99%
“…[7] In CuCAAc a polymer a-functionalized with an azide and another polymer chain carrying an v-alkyne can readily be reacted to generate block copolymers. [8] An alternative pericyclic method of conjugating two polymer chains is connecting them via a Diels-Alder or hetero DielsAlder reaction. [9][10][11][12][13] For the present study, however, the method of ligation is of no concern-as long as the reaction is rapid on the time scale of potential diffusion effects-as we will assume an ideal process, where two polymer chains react immediately and quantitatively with their a-and v-ends as soon as they meet.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, we have demonstrated that the conjugation of two mono-modal initial size-exclusion chromatography (SEC) distributions can lead to multi-modal conjugated distributions depending on their initial number average M n , weight average M w , and thus PDI. [8] The simulations of the convolutions were carried out under statistical conditions, i.e., each and every single polymer chain was able to react with another with identical rates no matter how many monomer units these chains carried. The motivation for the present study stems from the fact that the polymerpolymer ligation reaction displays similarities to the bimolecular termination process in free-radical polymerization (FRP)-a diffusion controlled process.…”
Section: Introductionmentioning
confidence: 99%